Bringing Academic and Corporate Worlds Closer: We Need Pracademics. (May 2014) - Panda, Abinash
I have shared my learning from my professional stints with both academic world and the world of practice. My stint with the corporate world has significantly shaped my thinking, behaviour and attitude to a significant extent. I developed empathy for both the communities and appreciated the viewpoints and perspectives of both an academic scholar and a practitioner. I started thinking both like an academic scholar as well as a practitioner. I do not claim myself to be a pracademic. But, I am sure a group of pracademics would help bridge the gaps between the worlds of theory and practice as they embody the merged role, carved out of two independent and differentiated roles of an academic scholar and a practitioner. In this article, I have presented an approach for grooming a group of pracademics with ambidextrous mindset, who would act as boundary spanners to bring both the worlds closer. This article also throws light on how is a pracademic different from a full-fledged practitioner or an academic scholar, how does a pracademic help bridge the gaps and how to groom pracademics. Grooming pracademics has its own challenges, when both corporate India and the Indian academic community are not ready yet for pracademics. These challenges and some of the ways of dealing with them are presented in this article.